Factors Affecting Online Shopping Behaviour of Boutique Products in Kathmandu Valley - Sah, Gunja Kumari (Dristikon: A Multidisciplinary Journal, 2021)
The Internet significantly influences people's beliefs and habits all around the world. As a result of this blessing, online shopping has flourished, influencing the lives of ordinary people. This research aims to learn more about how people shop for boutique products online and identify the major influential factors. The research was constructed using a positivist approach and a descriptive and causal research design. Data were obtained from the 325 samples of respondents at Kathmandu valley through convenience sampling techniques. A total of 450 structure questionnaires were distributed, and 360 were returned. 35 questionnaires were judged to be invalid, while the remaining 325 were referred to as valid questionnaires, entered into SPSS version 20 for the analysis. The result revealed that trust, firm reputation, and ease of use are significant at a 5percent level of significance. However, there was an insignificant relationship between price and online shopping behaviour. Firm reputation and ease of use were the major influential factor of online shopping of boutique products. The study will help the boutique business to develop their strategies as per the consumer need.